Transformations and tensions in sustainability work - Houtbeckers, Eeva; Salmenniemi, Suvi; Räikkönen, Timo (Informa UK Limited, 2025)
A global sustainability transformation called by The United Nations 2030 Agenda for Sustainable Development has important implications for the organisation of production, and structures and processes of work. However, recent scholarship has raised a need to make sense of how everyday work processes are changing to meet sustainability demands and of the factors that may facilitate or hinder this development. Therefore, this article focuses on the workplace as a meaningful site of sustainability transformation and explores practices of sustainability work in Finnish business organisations. We examine how sustainability is done in the everyday practices of these organisations and the kinds of tensions emerge. Sustainability work means practices with which business organisations seek to make their activities more ecologically sustainable. Drawing on interviews with representatives of organisations involved in Climate Leadership Coalition business network and engaging with practice theorising and the literature of strong and weak sustainability, we identify four practices of sustainability work - improving, monitoring, mediating, and mainstreaming - and highlight the tensions involved in them. We conclude that these practices are largely characterised by 'weak' sustainability and remain within the remit of ecological modernisation, indicating that sustainability work in organisations is not yet sufficiently aligned with planetary boundaries.